Protein profiles identified by LC-MS/MS demonstrate change in beta oxidation, ketogenesis, and propionate metabolism in rumen epithelium with different additives - Rocha, Leone Campos [UNESP]; Assunção, Andrey Sávio de Almeida [UNESP]; Martins, Renata Aparecida [UNESP]; Carvalho, Victor Valério de; Perdigão, Alexandre; Buzalaf, Marília Afonso Rabelo; Adamec, Jiri; Braga, Camila Pereira; Millen, Danilo Domingues [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Elsevier, 2023)
Replacement of ionophore feed additives by essential oils demonstrates differences in energy metabolism. The mechanism of action of essential oils depends on the ruminal pH, therefore, feedlot diets with high starch inclusions tend to show greater effectiveness of these natural additives. The aim of this study is to map the proteome of the ruminal epithelium of feedlot Nellore cattle (n = 60) with different additives (monensin, blend of essential oils + exogenous α-amylase) and varying levels of starch (25% and 45%) Two-dimensional polyacrylamide gel electrophoresis was used to separate the proteome of ruminal epithelium. The differentially expressed protein spots were characterized by isoelectric point, molecular mass, volume, and intensity of the spots and identified by liquid chromatography tandem mass spectrometry (LC-MS/MS). Diets using an essential oil blend associated with exogenous amylase promoted greater expression of macromolecules from the degradation of carbohydrates through the glycolytic and ketogenesis pathway. Fourteen proteins were identified in upregulation and the presence of proteins involved in glucose oxidation as well as Hydroxymethylglutaryl–CoA lyase (HMGCL), which catalyzes part of the metabolic intermediate metabolism—a key step in ketogenesis. Our results suggest that there was an increase in glycolysis from the oxidation of Glyceraldehyde-3-phosphate dehydrogenase (GAPDH GAPD), which participates in the first step of acetate and butyrate production and the oxidative decarboxylation of the ruminal epithelium of feedlot Nellore cattle. Monensin increased precursors of propionate, such as methylmalonyl-CoA mutase (MUT), which suggests greater synthesis of propionate via propionyl-CoA upon entry into the citric acid cycle as succinyl-CoA, which can increase feed efficiency and reduces feed intake.
Keywords: Energy metabolism; Mass spectrometry; Monensin; Propionate